Pengaruh Work Life Balance dan Dukungan Sosial terhadap Kesehatan Mental Karyawan Perempuan di SPBU Makassar - Nur Anisa; Andi Risfan Rizaldi; M.Yusuf K (Universitas Kristen Indonesia Toraja, 2026)
This study aims to determine the effect of work-life balance and social support on the mental health of female employees at gas stations in Makassar. Mental health is an essential factor influencing employee well-being, productivity, and work performance, particularly for female employees who often face the dual responsibilities of work and family life. This study employed a quantitative research method by distributing structured questionnaires to 96 female employees working at gas stations in Makassar. The collected data were analyzed using multiple linear regression and t-test to examine the influence of each independent variable on mental health. The results revealed that work-life balance had a negative and significant effect on mental health, with a t-value of -4.921 and a significance level of 0.000 (<0.05). Meanwhile, social support had a positive and significant effect on mental health, with a t-value of 3.805 and a significance level of 0.000 (<0.05). These findings indicate that social support plays an important role in improving employees' mental health, while an imbalance between work and personal life may negatively affect psychological well-being. Therefore, organizations are encouraged to strengthen social support systems and implement policies that promote a healthier work-life balance to enhance employee mental health and overall organizational performance.